NATIONAL PECULIARITIES OF THE WORLD LINGUISTIC PROCESS - Sabirova Dilshoda (Western European Studies, 2025)
The article examines the national peculiarities of the world linguistic process, as well as the problems of the linguistic picture of the world. It notes that the linguistic picture of the world is a set of knowledge about the world that is reflected in the language, and the linguistic picture of the world reflects the national and cultural specificity of the worldview of the people.
Keywords: linguistic process; national features; consciousness